Enzymatic Potential of Schizophyllum commune BNT39 in BHET Hydrolysis and PET Biodegradation - Martínez, Fernando Gabriel (2025)
The accumulation of polyethylene terephthalate (PET) in the environment demands efficientmicrobial strategies for its degradation. This study evaluates the biodegradation potentialof Schizophyllum commune BNT39 toward bis(2-hydroxyethyl) terephthalate (BHET),a major PET intermediate, and PET itself. Clear halos on BHET-agar plates indicatedextracellular hydrolytic activity. In liquid culture, thin-layer chromatography (TLC) andhigh-performance liquid chromatography (HPLC) analyses revealed a three-phase degradationprofile characterized by rapid BHET hydrolysis, transient dimer accumulation, andsubsequent conversion to terephthalic acid (TPA). BHET was reduced by approximately96% within seven days, while TPA accumulation reached 0.8 mg/mL after 30 days ofincubation. Although PET degradation was limited, TPA was consistently detected as theprincipal product, with no BHET or MHET intermediates. To explore strategies for enhancingenzymatic activity, apple-derived cutin, PET, BHET, and polycaprolactone (PCL) weretested as inducers. Cutin markedly stimulated extracellular enzyme production, suggestingactivation of cutinase-like enzymes. Overall, S. commune BNT39 demonstrates the ability totransform PET-related substrates, with cutin emerging as a promising natural stimulant toenhance enzymatic depolymerization. Future studies should focus on enzyme purification,activity profiling, and reaction optimization near PET’s glass transition temperature, wherethe polymer becomes more accessible for enzymatic attack.